2011
DOI: 10.1038/leu.2011.245
|View full text |Cite
|
Sign up to set email alerts
|

Impact of arsenic trioxide in the treatment of acute promyelocytic leukemia

Abstract: Arsenic trioxide (ATO) is presently the most active single agent in the treatment of acute promyelocytic leukemia (APL). This review provides insights into the mode of action and the pharmacological properties of ATO, and summarizes the most relevant results of more than 20 treatment studies in relapsed or newly diagnosed APL published between 1997 and 2011. ATO acts by targeting multiple pathways in APL leading to apoptosis and myeloid differentiation. It induces complete remission without myelosuppression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
102
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(105 citation statements)
references
References 89 publications
0
102
0
Order By: Relevance
“…Acute and chronic GVHD were defined and scored according to the Glucksberg and National Institutes of Health consensus criteria, respectively. [15][16][17] TRM was defined as death from any cause without evidence of relapse or progression of the original disease. Progressionfree survival (PFS) was defined as the interval from HSCT to either relapse or progression or death in remission (whichever came first).…”
Section: Org Frommentioning
confidence: 99%
“…Acute and chronic GVHD were defined and scored according to the Glucksberg and National Institutes of Health consensus criteria, respectively. [15][16][17] TRM was defined as death from any cause without evidence of relapse or progression of the original disease. Progressionfree survival (PFS) was defined as the interval from HSCT to either relapse or progression or death in remission (whichever came first).…”
Section: Org Frommentioning
confidence: 99%
“…9 It has also been postulated that the bortezomib-induced increases in ROS levels in tumor cells may be the basis for its synergy with other chemotherapeutic agents. 9,23 Arsenic trioxide (ATO) has emerged as the most active single agent in the treatment of acute promyelocytic leukemia, 24 and ATO-based therapies are being investigated in other cancers including other hematopoietic malignancies. [25][26][27][28][29] Although the mechanisms underlying ATO-induced cytotoxicity are not completely understood, ATO-mediated induction of ROS has been shown to reduce the membrane potential of mitochondria, enhance the release of cytochrome c and induce both caspasedependent and caspase-independent apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Lengfelder et al described arsenic trioxide as very potent and first line agent in treatment of APL. [7] Chiang et al studied the action of ATO on guinea pig papillary muscle and the study concluded that dose dependent IV infusion of ATO prolonged QT interval and action potential duration (APD). [8] The study suggested that Arsenic trioxide has direct effect on cardiac repolarisation and the drug must be administered with strict ECG monitoring.…”
Section: Ecg Monitoring Recommendations and Precautionsmentioning
confidence: 99%